The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.36347/sjams.2022.v10i04.003
|View full text |Cite
|
Sign up to set email alerts
|

Workplace Violence against Nursing Student and Nurses: in Taif Mental Health Hospital: A Cross-Sectional Survey

Abstract: Background: Nursing students and nurses have been subjected to workplace violence has become another challenge at medical care facilities. The issue isn't restricted to specific parts of the world; its pervasiveness is expanding around the world. Objectives: to look at impact and consequences of violence among nurses and nursing students to make a preventive strategy and assess the phenomenon. Material and Methods: In Taif's mental health hospital, a cross-sectional hospital-based survey was conducted. At the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Other studies with comparable findings revealed that most of the perpetrators of violence were the patient's relatives (51.9%) and the majority of perpetrators were male (88.9%). 21,22 Regarding the factors that influence the incidence of violence, most of the time violence occurred by the patient's attendants (83.3%), the male perpetrator (100.0%), frequency of incidences was ≥2 times (16.7%), and at morning shift (66.7%). Factors related to the organization that influences violence, the most prevalent factors were lack of workforce (100.0%), high workload (83.3%), and lack of security (33.3%).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies with comparable findings revealed that most of the perpetrators of violence were the patient's relatives (51.9%) and the majority of perpetrators were male (88.9%). 21,22 Regarding the factors that influence the incidence of violence, most of the time violence occurred by the patient's attendants (83.3%), the male perpetrator (100.0%), frequency of incidences was ≥2 times (16.7%), and at morning shift (66.7%). Factors related to the organization that influences violence, the most prevalent factors were lack of workforce (100.0%), high workload (83.3%), and lack of security (33.3%).…”
Section: Discussionmentioning
confidence: 99%
“…Nurses mostly handled these situations themselves whereas students often called for help and/or activated alarms. 12 In Oman, a 2020 study by Al Maskari et al . examined the prevalence of violence directed at emergency department nurses.…”
mentioning
confidence: 99%
“…Nurses mostly handled these situations themselves whereas students often called for help and/or activated alarms. 12 In Oman, a 2020 study by Al Maskari et al examined the prevalence of violence directed at emergency department nurses. The study revealed that a significant majority of nurses, accounting for 87.4%, experienced some form of violence.…”
mentioning
confidence: 99%